Nutrition assistance of breastfeeding and complementary feeding associated with the linier growth of stunted children aged 6-24 months - Simbolon, Demsa; Ludji, Ina Deborah; Rahyani, Yuni (Universitas Udayana, 2022)
Background and purpose: Age 6-24 months is a critical period for experiencing nutrition and health problems, especially among children who are stunted. Stunting children need to recover their nutritional status through appropriate interventions to be able to pursue their growth. The purpose of this study was to determine the effect of nutrition assistance on breastfeeding and complementary feeding on the length growth of children aged 6-24 with stunting. Methods: This was a quasi-experimental study. A sample of 60 intervention and 60 control groups were divided into North Bengkulu District and Timor Tengah Selatan (TTS) District. Nutrition assistance for 6 months (July-November 2019) was carried out by 10 trained cadres. Each cadre is responsible for 6 stunted children aged 6-24 months (3 children received assistance and 3 children with standard services from the public health center). Data analysis uses independent t-test and dependent t-test after passing the homogeneity test phase of the proportion of sample characteristics and normality of the data. Results: We found that assistance for breastfeeding and complementary feeding for mothers with stunting children aged 6-24 months was effective in increasing the growth of the child's body length. As many as 53.3% of stunted children in North Bengkulu District and 36.7% in TTS District showed growth after nutrition assistance. Conclusion: It is recommended that the implementation of a nutrition assistance model be accompanied by continuous family and community empowerment in the recovery of nutritional status, especially in families with stunted children aged 6-24 months.